ANALISIS KELAYAKAN USAHA PENGOLAHAN HHBK PALA PADA KELOMPOK TANI HUTAN AKE GURACI DI KELURAHAN MARIKURUBU - Fatmawati Kaddas; Firlawanti Lestari Baguna (Komitmen: Jurnal Ilmiah Manajemen, 2023)
One of the non-timber forest product spice groups that have economic value is nutmeg. This study aims to analyze the feasibility of a nutmeg processing business developed by the Ake Guraci Forest Farmers Group, Marikurubu Village. The research will take place in 2021. The research data is in the form of primary and secondary data. Primary data collection techniques using interviews with informants and observation; Meanwhile, this secondary data is in the form of information related to the market price of materials supporting the processing of nutmeg flesh, permits, and other related documents. The data collected will be analyzed using business feasibility analysis. The results of the feasibility analysis show that the non-financial processing of nutmeg meat based on the criteria of legal aspects is feasible. While the results of the financial feasibility analysis are based on acceptance criteria for the types of products that are feasible to develop, namely the types of crackers, paltar, crackers, candy, and jam product’s. While based on the criteria for the benefits of a feasible type of product except for candy products. So that the selling price and production riots are factors that influence the development of the nutmeg meat food production business.